Usulan Indikator Evaluasi Pemasok dalam Penetapan Bidder List: Studi Kasus Pengadaan Jasa PT. Semen Padang - Pri Gustari Akbar; Henmaidi Hadiguna; Elita Amrina (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2015)
Each company will seek to improve performance in order to obtain the optimal results and customer satisfaction. One of the factors that affect the performance of the company is the supplier or vendor, which acts as a supplier of the operational needs of the company consisting of raw materials and spare parts manufacturing equipment. The existence of suppliers is crucial for the production process and the product to be produced. Therefore, it is necessary to a proper selection of suppliers so as to eliminate all risks that would result in losses for the company. PT. Semen Padang is one of the companies involved in the cement industry is one of the members of PT. Cement Indonesia as the Holding Company. Until now both PT. Semen Padang and PT. Cement Indonesia does not have yet a standard method in the selection of suppliers for the procurement process of goods and services. This study aims to design the proposed indicator in the evaluation of suppliers to determine the bidder's list on a tender for the procurement of services in PT. Semen Padang. Based on the literature study, it obtained six criteria i.e: quality, delivery, performance history, price, technical capability, and procedural compliance, which are divided into 13 indicators of performance evaluation. These indicators will be validated by the cement industry. Future studies will design a model of evaluation of suppliers using Analytic Hierarchy Process (AHP) method to determine the bidder's list on a tender for the procurement of services in PT. Semen Padang.